Customary governance of artisanal and small-scale mining in Guinea: Social and environmental practices and outcomes⋆. (March 2021) - Huntington, Heather; Marple-Cantrell, Kate
Highlights: Clarifies complex tenure regime that governs artisanal mining of diamonds in Guinea. Insights about when statutory versus customary systems are applied and enforced. Identifies barriers to formalization efforts within small-scale mining communities. Highlights strength and weakness of customary governance regime for land management. Abstract: In Guinea, attempts are underway by international donors, development practitioners, and the national government to bring artisanal and small-scale diamond mining in line with a formal regulation and parcel allocation system. This formalization initiative in Guinea—along with similar reforms aimed at land tenure regularization across Africa—attempt to superimpose modern legal institutions onto community institutions. Artisanal and small-scale mining (ASM) in Guinea's Forécariah and Kindia regions is currently governed by customary governance structures and deeply rooted customary institutions for land and property rights management. Thus far, formal structures have failed to replace or integrate with customary institutions. Identifying how to achieve complementarity between informal and formal systems that are defined by deep cultural and structural tensions requires a solid understanding of customary institutions (Ensminger, 1997). This paper analyzes social and environmental practices and ASM outcomes in an area with a history of strong informal customary governance. The study has three research objectives. First, the study seeks to provide a deeper understanding of the customary institutions and systems governing ASM in Guinea's Forécariah and Kindia regions. Second, the paper draws on empirical analysis of village level quantitative and qualitative data to identify whether and how customary governance and institutional factors affect social and environmental outcomes in the context of ASM. Based on these findings, the paper closes with concrete policy recommendations for promoting greater complementarity between the formal and informal systems. Given the scale and scope of quantitative and qualitative data sources applied to the analysis, this study utilizes the most comprehensive empirical data to-date on ASM in a customary context. As such, this paper presents a unique contribution to the literature around customary governance, resource contestations, and land governance for mining communities and the ASM sector in sub-Saharan Africa.